1977
DOI: 10.1002/aic.690230102
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic regeneration of ATP: II. Equilibrium studies with acetate kinase and adenylate kinase

Abstract: Equilibria of reactions catalyzed by acetate kinase and adenylate kinase were studied experimentally and theoretically. Nucleotide conversions in excess of 90% were obtained with reactants (acetyl phosphate and one nucleotide) in stoichiometric proportion for ATP regeneration from either ADP via acetate kinase or AMP via the coupled enzyme system. Observed equilibrium constants, measured as a function of [Mg*+] at pH 7.4, ranged from about 1 to 9 for the reaction catalyzed by adenylate kinase and from about 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Free Mg 2+ ion concentrations were calculated by an algorithm written according to a previously proposed method (Storer and Cornish-Bowden, 1976), which is based on iteratively solving ionic species mass balance equations. The dissociation constants applied in this method for complex formation between dissolved ions and low-molecularweight system components were taken from Langer et al (1977) unless otherwise noted: K HNTP ‫ס‬ 1.26 и 10 −7 M, K H 2 NTP ‫ס‬ 8.71 и 10 −5 M, K Mg 2 NTP ‫ס‬ 5.01 и 10 −2 M, K MgNTP 2 ‫ס‬ 3.98 и 10 −3 M, K MgNTP ‫ס‬ 1.15 и 10 −5 M (O'Sullivan and Perrin, 1964), K MgHNTP ‫ס‬ 1.41 и 10 −3 M (O'Sullivan and Perrin, 1964), K MgPi ‫ס‬ 1.32 и 10 −2 M (Smith and Alberty, 1956), K MgPPi ‫ס‬ 1.70 и 10 −5 M (Käpylä et al, 1995), and K Mg 2 PPi ‫ס‬ 2.14 и 10 −3 M (Käpylä et al, 1995). The employed buffer, Tris, was shown to exhibit no significant binding capacity to metal ions (Good et al, 1966).…”
Section: Methodsmentioning
confidence: 99%
“…Free Mg 2+ ion concentrations were calculated by an algorithm written according to a previously proposed method (Storer and Cornish-Bowden, 1976), which is based on iteratively solving ionic species mass balance equations. The dissociation constants applied in this method for complex formation between dissolved ions and low-molecularweight system components were taken from Langer et al (1977) unless otherwise noted: K HNTP ‫ס‬ 1.26 и 10 −7 M, K H 2 NTP ‫ס‬ 8.71 и 10 −5 M, K Mg 2 NTP ‫ס‬ 5.01 и 10 −2 M, K MgNTP 2 ‫ס‬ 3.98 и 10 −3 M, K MgNTP ‫ס‬ 1.15 и 10 −5 M (O'Sullivan and Perrin, 1964), K MgHNTP ‫ס‬ 1.41 и 10 −3 M (O'Sullivan and Perrin, 1964), K MgPi ‫ס‬ 1.32 и 10 −2 M (Smith and Alberty, 1956), K MgPPi ‫ס‬ 1.70 и 10 −5 M (Käpylä et al, 1995), and K Mg 2 PPi ‫ס‬ 2.14 и 10 −3 M (Käpylä et al, 1995). The employed buffer, Tris, was shown to exhibit no significant binding capacity to metal ions (Good et al, 1966).…”
Section: Methodsmentioning
confidence: 99%
“…The average of the relative deviation between the measured and the calculated total volume of titrant taken over all progress curves was 0.047 for the selected set in Table 2. A set of constants including the values given by Alberty (1968) yielded a value of 0.069, and a set including the constants given by Langer et al (1977) yielded 0.076. Table 3 shows the abbreviations used for the different ligands.…”
mentioning
confidence: 99%
“…The concentrations of MgATP2-, MgADP-, protonated complexes and other ions were calculated from the total concentrations of MgCl2, ATP, ADP and other substances as described by Storer & Cornish-Bowden (1976a), by using the thermodynamic data of Phillips et al (1966) and the data cited in a paper by Langer et al (1977). Calculation showed that the MgATP2concentration was a high and nearly constant proportion (74 + 2 %) of the total ATP concentration, and that the MgADP-concentration was also a nearly constant proportion (94±1 +%) of the total ADP concentration.…”
Section: Concentrations Of Complex Ionsmentioning
confidence: 99%